Basic and new aspects of gastrointestinal ultrasonography - Ødegaard, Sverre, 1947-; Gilja, Odd Helge; Gregersen, Hans, 1962- (Advanced series in biomechanics, 2005)
This book is an introduction for students and young doctors at thebeginning of their career in diagnostic ultrasonography. It alsopresents the latest in innovations and techniques in gastrointestinalultrasonography. The reader will find basic aspects of ultrasonographyas well as highly advanced technical and research papers.